TECH ENTREPRENEURS AND DISRUPTIVE INNOVATION: TRANSFORMING TRADITIONAL INDUSTRIES - Shah, Aditee Huparikar; Pawar, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Technology entrepreneurs have significantly transformed traditional industries by implementing disruptive innovations that alter market structures and customer habits. This study examines the influence of technology entrepreneurs on conventional industries, focusing on the primary catalysts of disruptive innovation, strategies for industry adaptation, and economic consequences. This study utilizes a sample of 150 respondents and performs quantitative data analysis to evaluate the responses of traditional firms to technology disruptions and the influence of entrepreneurial strategies on market transformation. The results indicate that disruptive innovations threaten existing enterprises while also generating new prospects for cooperation and market growth. The study emphasizes the need for traditional industries to implement agile strategies, invest in technology, and adopt digital transformation to maintain competitiveness in the changing market environment.